Preparation of high-solubility rice protein using an ultrasound-assisted glycation reaction. (November 2022) - Chen, Xiuwen; Zhao, Hongqing; Wang, Hong; Xu, Pinji; Chen, Maolong; Xu, Zhou; Wen, Li; Cui, Bo; Yu, Bin; Zhao, Haibo; Jiao, Ye; Cheng, Yunhui
Graphical abstract: Highlights: Ultrasound accelerated the glycation reaction between rice protein and dextran. Ultrasound promoted a looser and more flexible rice protein structure. Ultrasound-assisted glycation improved solubility of rice protein significantly. Abstract: To date, the poor solubility of rice protein (RP) has limited its industrial application in food products. This study aimed to prepare high-solubility RP conjugates using ultrasound-assisted glycation between RP and dextran. The conditions of glycation, treatment at 82 °C for 22 min under 600 W ultrasonic power, were optimized using single-factor experiments and response surface analysis. The solubility of the conjugates reached 90.6 %. Compared with traditional wet-heating glycation, ultrasound-assisted treatment brought more high-molecular-weight components, higher degree of graft, and less contents of arginine and lysine, indicating that ultrasound accelerated the glycation reaction. Ultrasound also resulted in a looser and more flexible structure of RP, manifesting in a 10 % reduction in β-sheets and 10.6 % increase in random coils of conjugates. The analysis of fluorescence and surface hydrophobicity indicated that ultrasound increased the exposure of hydrophobic residues towards aqueous environment. Besides solubility, the foaming and emulsifying properties of RP were improved through conformational changes. In summary, ultrasound-assisted glycation was found to be an efficient and green method for preparing high-solubility RP conjugates.